Diagnostic diversity: The role of social class in diagnostic experiences of infertility. Issue 4 (22nd October 2013) - Bell, Ann V.
Abstract Research in the area of the sociology of diagnosis has recently expanded. Despite this development, the foundations of the social aspects of diagnoses, including race, class and gender, are relatively unexplored. Understanding such diversity is important, however, as researchers have shown that diagnoses have significant repercussions on the illness experience. This article is an effort to overcome this gap in the literature by examining class diversity in interpretations and understandings of diagnoses. Using the medicalised condition of infertility as a case example of class differences around diagnoses, I conducted 58 in‐depth interviews with infertile women of various class backgrounds in the USA. By comparing the lived experiences of infertility between higher and lower class women, I explore differences in the understanding, interpretation and outcomes of diagnoses, specifically. Furthermore, among lower class women, I examine how they understand infertility outside the medical diagnostic framework. The findings reveal how interpretations and experiences of diagnoses vary depending on an individual's social location. In other words, the study demonstrates that class matters in terms of diagnoses and their understanding.